PREVENTION OF ISCHEMIC HEART DISEASE - Ninković, Olivera; Grujičić Šipetić, Sandra (HEALTH CARE, 2025)
Ischemic heart disease (IHD) is the leading cause of death globally, while in Serbia, it is responsible for more than 45% of all deaths, which is significantly above the average in the European Union. It occurs as a result of atherosclerosis of coronary arteries, and the main risk factors include smoking, hypertension, dyslipidemia, diabetes, obesity, physical inactivity, unhealthy diet and stress. Prevention as the foundation of public health and health policies of each country includes a range of measures and activities aimed at preserving and improving health, preventing the occurrence of diseases and complications, as well as reducing mortality and disability in the population at the primordial, primary, secondary and tertiary level. Key measures include the adoption of healthy lifestyle habits: balanced Mediterranean diet, regular physical activity (at least 150 minutes of moderate exercise per week), maintaining a healthy weight and quitting smoking. Controlling biological risk factors, such as hypertension, diabetes and high cholesterol, is also essential. A screening program within primary prevention plays an important role in the early detection of individuals at increased risk for IHD. Secondary prevention includes adequate treatment and measures to prevent further complications in patients who already suffer from IHD. This includes pharmacological therapy (antiaggregation drugs, beta-blockers, statins), invasive procedures such as coronary interventions or bypass surgery, as well as changing unhealthy habits. Tertiary prevention is aimed at patient rehabilitation, the reduction of complications and the improvement of the quality of life. Although recommendations for prevention are clearly defined, their implementation emerged as a challenge in Serbia. Better coordination, continuous education of the population and improvement of the health care system, especially in the field of post-hospital rehabilitation, are necessary. A comprehensive, integrated approach that includes public health and medical interventions is crucial for the long-term reduction of the burden of IHD in Serbia.
Keywords: cardiovascular diseases, ischemic heart disease, acute coronary syndrome, prevention, risk factors